Risk communication and caring behavior related to patient satisfaction: A cross-sectional study at the Mangusada Regional Hospital, Badung District, Bali Province, Indonesia - Mas Manik Astawastini, I Dewa Ayu; Januraga, Pande Putu; Ani, Luh Seri (Universitas Udayana, 2024)
Background and purpose: The quality of hospital services during the COVID-19 pandemic tends to decline. This can affect patients’ satisfaction in carrying out treatment and care. Risk communication and caring behavior are important aspects that can affect patient satisfaction. The purpose of our study was to determine the relationship between risk communication and caring behavior of nurses with patient satisfaction on internal medicine polyclinic in the Mangusada Regional Hospital, Badung District, Bali Province, Indonesia. Methods: Our research design is analytic observational with cross sectional approach. We conducted research at the internal medicine polyclinic of the Mangusada Regional Hospital, Badung District from March 1 to April 21, 2022. Samples of our study were 120 patients who visited the internal medicine polyclinic. Variables of our study which include patient characteristics, risk communication and caring behavior were collected using a questionnaire and analyzed with univariate, bivariate and multivariate approach using multiple logistic regression test with 95% confidence interval. Results: The study revealed that 52.5% of patients had low satisfaction, 54.2% of patients perceived low risk communication and 54.2% of patients perceived low caring behavior. There is a relationship between nurse risk communication with patient satisfaction (aOR=5.2; 95%CI: 1.9-14,3, p=0.001) and nurse caring behavior with patient satisfaction (aOR=9.8; 95%CI: 3.7 – 26,0, p=0.000). Conclusion: Risk communication and nurse caring behavior are related to patient satisfaction at internal medicine polyclinic in the Mangusada Regional Hospital, Badung District. This underscores the importance of focusing on improving care practices and communication strategies to enhance patient satisfaction. It also emphasizes the need to ensure the good ratio of health care workers to the number of patients in order to provide quality health services.